Markedness and faithfulness in vowel systems - Miglio, Viola, 1966- (Outstanding dissertations in linguistics., 2005)
Miglio argues that to assess the relative markedness of a segment, frequency of occurrence in vowel inventories is insufficient when considered on its own. In its analysis of the Great Vowel Shift, this book elaborates a more useful model of a unitary change even in a surface-oriented theory such as optimality theory, with the help of local conjunction. Miglio extends the device of local conjunction to model opaque relations, and calls for reranking and lexicon optimization as the means to capture change within optimality theory.